Slovak Republic : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
From this study, it is noted that accounting, classification, and reporting of fiscal operations would benefit from the establishment of a state treasury, and a number of measures were recommended. The report on the Observance of Standards and Codes (ROSC) concluded that key weaknesses in budget preparation had been largely addressed, and that budget preparation was cast against a clearly identified medium-term macroeconomic framework and constraints, and that the integrity of publicly available information on public finances was ensured by clearly defined and independent scrutiny.